Investment facilitation at the WTO is not investment redux - Khalil Hamdani (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2018)
Discussion of investment facilitation at the WTO should enhance the development dimension of the Trade Facilitation Agreement. It should be focused, open-ended, inclusive, and allow for individual country implementation capacity. It should engage trading partners in capacity building of weaker members. It should envisage a counterpart Investment Facilitation Agreement.
Keywords: 330